Development of Biosensor for Catechol Using Electrosynthesized Poly(3‐methylthiophene) and Incorporation of LAC Simultaneously. Issue 9 (12th August 2014) - Sethuraman, V.; Muthuraja, P.; Sethupathy, M.; Manisankar, P.
Abstract Simultaneous electropolymerization of 3‐methylthiophene and incorporation of Laccase (LAC) was carried out in the presence of propylene carbonate as a medium by amperometric method. This enzyme modified electrode was used for the sensing of polyphenol. Catechol is taken as a model compound for the study. UV‐Vis spectral studies suggest no denaturation of LAC in presence of propylene carbonate. The SEM studies reveal the surface morphology and incorporation of LAC in P3MT with agglomerated flaky masses are observed in with and without enzyme micrographs. The cyclic voltammograms were recorded for 0.01 mM catechol on plain glassy carbon, polymer and enzyme incorporated electrodes at pH 6.0 and scan rate 50 mV s−1. The fabricated electrochemical biosensor was used for the determination of catechol in aqueous solution by Differential Pulse Voltammetry (DPV) technique. The concentration linear range of 8×10−8 to 1.4×10−5 M a value of MichealisMenten constant Km=7.67 µmol dm−3 and activation energy is 32.75 kJ mol−1. It retains 83 % of the original activity after 60 days which is much higher than that of other biosensors. The developed biosensor was used to quantify catechol in the determination in real samples.